1959
DOI: 10.1103/physrevlett.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Free Induction Decays of Rotating Solids

Abstract: H * 0) can be created through the use of second or higher Born approximations. Because of the extreme smallness of the scattering length as compared to the de Broglie wavelength of the neutron, it is reasonable to expect that the cross section for emitting any transverse wave should be much smaller than the corresponding cross section for a longitudinal wave. Thus, the existing measurements of total cross sections 2 > 4 already give an indication that these excitations are longitudinal waves. However, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
640
0
6

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,105 publications
(652 citation statements)
references
References 3 publications
6
640
0
6
Order By: Relevance
“…94,97,98 Additionally, the tissue samples remain intact after the spectral acquisition and can be further analyzed by histopathology, proteomics or gene expression. 99 Commonly, a standard water-presaturated NOESY experiment, a T 2 -weighted CPMG experiment, J-resolved and sometimes di usion edited sequences (DIFF) are used in metabolomics experiments.…”
Section: Nmr Spectroscopy Of Bio Uids and Tissuesmentioning
confidence: 99%
“…94,97,98 Additionally, the tissue samples remain intact after the spectral acquisition and can be further analyzed by histopathology, proteomics or gene expression. 99 Commonly, a standard water-presaturated NOESY experiment, a T 2 -weighted CPMG experiment, J-resolved and sometimes di usion edited sequences (DIFF) are used in metabolomics experiments.…”
Section: Nmr Spectroscopy Of Bio Uids and Tissuesmentioning
confidence: 99%
“…6 MAS can eliminate the chemical shift anisotropy when the sample rotation axis is inclined 54.71 to the external magnetic field and the spinning frequency of the rotor is larger than the chemical shift anisotropy. 18,19 We observed that sample spinning generates pressure for the fully hydrated sample as a function of the square of the rotor-spinning frequency and radius because the centrifugal force is divided by the wall area of the rotor. Pressure-induced protein structure, cell-volume changes, pharmaceutical samples and rubbers have all been characterized using fast MAS techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In order to extract useful information (for instance the isotropic chemical shifts and the second order isotropic shifts arising from quadrupolar interactions), it is necessary to have a high resolution spectra consisting of isotropic shifts by eliminating the anisotropic broadenings owing to second order effects of the quadrupolar interactions in the central transitions with half integer spin nuclei. The first order inhomogeneous broadening which originates from this spin Hamiltonian can be efficiently averaged to zero by using magic angle spinning (MAS) [56,58]. However after applying MAS to a powder sample originating in second order quadrupolar interactions, the linewidth is only reduced by about a factor of three.…”
Section: Dynamic Angle Spinning (Das)mentioning
confidence: 99%
“…Unfortunately, the numerical simulations have not yet been accomplished and are left for future work. [56,57,58], dynamic angle spinning (DAS) [78,76], double rotation (DOR) [72,104]' and multiple pulse (MP) [114]. The principle involved in these methods is the coherently motional averaging under which the orientation dependence of the resonance frequency can be completely or partially removed, and the NMR spectra contain only the isotr<;>pic chemical shifts.…”
Section: -Lb{t) = :T B[mp(t)l1m(p)mentioning
confidence: 99%
See 1 more Smart Citation